A taxonomic revision of Taraxacum sect. Dissecta, a continental steppe group common in Siberia and adjacent regions of Central Asia - Kirschner, Jan; Štěpánek, Jan (Phytotaxa, 2023)
Steppe and similar habitats in southern Siberia, Mongolia and adjacent regions harbour a considerable diversity of Taraxacum sect. Dissecta (Asteraceae, Crepidinae); its taxonomic revision is presented. A thorough study of live and herbarium plants revealed 30 species that belong, or are very close, to T. sect. Dissecta; seven species were known previously and 23 are described as new, mostly from the Altai Republic, Novosibirsk, Irkutsk, Lake Baikal and Bratsk. Their distribution includes the Asiatic part of Russia, Kazakhstan, Kyrgyzstan, Mongolia and Xinjiang, China. The name T. dissectum (Ledeb.) Ledeb. is relegated to the synonymy of T. pubescens (Fr.) Fr. A detailed analysis of the original material of the name T. collinum revealed that it consists of mostly juvenile plants belonging to several species of T. sect. Dissecta, and that it requires further study on newly collected material. The frequently reported occurrence of T. sect. Dissecta (as T. dissectum) in the European mountain ranges was reassessed. The reports from the Pyrenees belong to T. pyrenaicum and related species of T. sect. Obliqua. Two mutually similar species, often referred to as T. dissectum, recognized as T. aquilonare Hand.-Mazz. and T. zermattense Dahlst., were studied in order to reconsider the hypothesis that they represent T. sect. Dissecta in the Alps. On the basis of morphological and phytogeographical data, we present this hypothesis as quite plausible but requiring experimental, phylogeographic evidence; a full treatment of both species is also given. The name T. compactum is typified and the species is excluded from T. sect. Dissecta; it belongs to T. sect. Qaisera.